A CRITICAL DISCOURSE ANALYSIS OF IDEOLOGICAL REPSENTATION IN DONALD TRUMP'S SPEECH AT THE 2025 WORLD ECONOMIC FORUM - Nabilah Amanda Sabrina (LINGUISTICA, 2026)
This research examines ideological constructions within Donald Trump's address to the 2025 World Economic Forum through Critical Discourse Analysis (CDA), utilizing Teun A. Van Dijk's Ideological Square framework (2011) alongside his 25 ideological discourse categories (2006). Analysis reveals Trump's speech employs strategic polarization, predominantly through positive in-group emphasis (63%) and negative out-group emphasis (27%), while minimizing in-group weaknesses (7%) and out-group strengths (3%). Qualitative textual examination uncovers prevalent deployment of rhetorical mechanisms including exaggeration, nationalistic valorization, and value-based assertions that construct a nationalist-populist discourse. Results indicate Trump's administration is discursively positioned as a revolutionary catalyst for American and global transformation, contrasted against portrayed inadequacies of prior leadership and international entities. Through analyzing these linguistic strategies, this research illuminates how political communication functions as an instrument for ideological construction and authority consolidation. This investigation enhances scholarly understanding of political rhetoric within international economic platforms, particularly regarding intersections of economic strategy, nationalism, and ideological division in constructing public consciousness and diplomatic relations.